Prevalence and risk factors for long COVID in China: A systematic review and meta-analysis of observational studies - Le-Yan Hu; An-Qi Cai; Bo Li; Ying-Qiu Sun; Zheng Li; Jian-Ping Liu; Hui-Juan Cao (Journal of Infection and Public Health)
Background: With the outbreak of COVID-19 in China, a large number of COVID-19 patients are at risk of long COVID after recovery. The purpose of our research is to systematically review the existing clinical studies to understand the current prevalence and related risk factors of long COVID in COVID-19 patients in China. Methods: The protocol of this systematic review was registered on PROSPERO (CRD42024519375). We searched six electronic databases from 1st January 2020–1st March 2024. Literature screening, data extraction, and risk bias assessment were independently carried out by two reviewers. Quality of the included studies was evaluated by AHRQ and NOS. The meta-analysis was performed by R software 4.2.3 to derive the prevalence of long COVID and risk factors. Results: Overall, 50 studies with 65880 participants were included. The results showed that the prevalence of long COVID (with at least one symptom) among the COVID-19 patients was approximately 50 % (95 %Confidence Interval (CI) 42–58 %) in China. Although we conducted meta-regression and subgroup analysis, the heterogeneity of the study was high. But the Omicron BA.2 variant had a statistically significant effect on the prevalence of long COVID (P = 0.0004). The three most common symptoms of long COVID were fatigue (0.33, 95 %CI 0.28–0.39), cognitive decline (0.30, 95 %CI 0.14–0.46) and shortness of breath (0.29, 95 %CI 0.15–0.43). Patients with severe acute phase of COVID-19 (Odds Ratio (OR) 1.57, 95 % CI 1.39–1.77), combined 2 comorbidities (OR 1.80, 95 % CI 1.40–2.32), combined 3 comorbidities (OR 2.13, 95 % CI 1.64–2.77), advanced age (OR 1.02, 95 % CI 1.01–1.04), female (OR 1.58, 95 % CI 1.44–1.73) were the risk factors for long COVID prevalence. Conclusion: Current systematic review found that nearly half of COVID-19 patients may suffering from long COVID in China. Establishing a long COVID recovery-support platform and regular follow-up would help to long-term monitor and manage the patients, especially those high-risk population.